Pertanggungjawaban Pidana Terhadap Anak Korban Pelecehan Seksual Yang Melakukan Pembunuhan dalam Perspektif Kriminologi - Irawan, Benny; Samallo, Caroline Estava (Universitas Sultan Ageng Tirtayasa, 2023)
The world of children is not always synonymous with playing. Sometimes children fall into criminal acts that make them face or conflict with the law. The crime of murder is committed by adults and can also be achieved by minors. One of the cases of this crime of murder occurred in Sawah Besar, Central Jakarta, where the perpetrators were minors and the child was also a victim of sexual harassment from the case different. This murder case is the first case in Indonesia, where the perpetrators of this murder are minors. Based on this, a problem arises: what factors cause the murder of children who are victims of sexual abuse from a criminological perspective? And what is the criminal responsibility for children who are perpetrators of murder who are victims of sexual abuse?. The framework of thought in this research is Psychological Theory and Criminal Liability Theory. This study uses a normative juridical method by examining legal library materials or secondary data, namely data that refers to legal norms, in-laws and regulations, legal theories, and court decisions that are then analyzed qualitatively. The research specifications in this study are descriptive analysis. This study concludes that the factor in the occurrence of the crime of murder committed by child victims of sexual abuse in a criminological perspective is because the ego aspect is more inclined to the id aspect and the superego aspect is weak and unable to balance the mind in overcoming inner conflict due to traumatic fear so that the superego aspect is not able to be a balancer in tackling internal disputes so that the occurrence of the crime of murder and in this case NF can be held criminally responsible with strict liability, seen from the actions of the defendant, namely violence against children that resulted in death, therefore the basis for making decisions by the judge that the defendant must be responsible for his actions by executing a sentence of imprisonment for two years. Suggestions for the government to conduct socialization to the community regarding the prevention of formal sexual harassment to apply it in the family environment to focus more on providing supervision and love to minimize deviations committed by children.